Knowledge and organizational performance in franchised restaurants in Colombia (2020)
Purpose: The aim of this study is to analyze the importance of knowledge in reaching organizational objectives (long-term organizational goals) and in constructing competitive advantage (value-added) and identifying the impact of this knowledge on organizational performance of franchised restaurants in an emerging market. Design/methodology/approach: Likert-scale surveys were applied to 50 managers representing 80% of the franchised restaurant business in Bogotá, Colombia. Data processing was performed through descriptive statistics, multiple correspondences analysis (MCA) and logit regression (LR). Findings: Results indicate that 1) of the set of factors that contribute to the achievement of franchise objectives, personnel motivation and continuous environmental scanning are the most important; 2) the primary sources of knowledge for construction of competitive advantage are clients and providers; and 3) the most significant impact of knowledge occurs in human resource and organizational development and in increased earnings. Practical implications: The study provides evidence of the role and the impact of knowledge in the performance of franchised restaurants and thereby contributes to academic analysis and managerial decision-making. Originality: This study provides aggregated and disaggregated analysis of empirical data on the role of knowledge in franchised restaurants, a sector with limited extant research in the context of emerging markets. © 2020, Emerald Publishing Limited.